EFFECT OF EXERCISE WITH CONTINUOUS AND INTERMITTENT BLOOD FLOW RESTRICTION ON HEMODYNAMICS - Silva,Hidayane Gonçalves da (2020)
ABSTRACT Introduction: Strength training with blood flow restriction (BFR) involves the use of low loads (20-30% of 1RM) with restriction of blood flow to promote gains in physical fitness. The restriction can be applied continuously or intermittently; however, it is unclear how it affects the hemodynamics of hypertensive women. Objective: To analyze the acute effect of resistance exercise (RE) on the upper and lower limbs with continuous and intermittent blood flow restriction (BFR) on the hemodynamic variables of women with hypertension. Methods: Thirteen women with controlled hypertension (40 to 65 years) underwent eight experimental protocols, with a randomized, counter balanced, crossover design; four exercise sessions for the right upper limb (elbow flexion) and four for the right lower limb (knee extension). The systolic arterial pressure (SAP), diastolic arterial pressure (DAP), and heart rate (HR) were measured before, during, immediately after and 15, 30, 45 and 60 minutes after the exercises. Results: There were no significant interactions between the protocols vs. segments vs. time, protocols vs. segments, protocols vs. time, segments vs. time, protocol, segment and time, on the variables SAP, DAP, and HR during and after the RE (p>0.05). Although all these protocols had significantly elevated SAP, DAP and HR, the values remained within the normal range. The protocols of this study did not cause hypotensive effect. Conclusion: Low-load RE combined with continuous and intermittent BFR, on the upper and lower limbs, appears to promote similar variations in the hemodynamic variables of women with hypertension. Level of evidence II; Randomized clinical trial.